Evaluation of hygienic quality and labelling of fish distributed in public canteens of Northeast Italy - Mariachiara Armani; Michele Civettini; Gabriella Conedera; Michela Favretti; Dorotea Lombardo; Rosaria Lucchini; Sabrina Paternolli; Alessandra Pezzuto; Michela Rabini; Giuseppe Arcangeli (Italian Journal of Food Safety, 2016)
Over the past few years, the demand for the introduction of fish products in public canteens (schools, hospitals and nursing-homes) has grown due to their good nutritional proprieties. The particular health conditions and sensitivity of some groups of consumers exposes them to greater risks of food poisoning. It is therefore important to monitor the raw materials that end up in mass catering implementing strategies of mass catering control, both with self-monitoring strategies and with regular controls performed by the competent health authorities. The purpose of this study is to assess the overall quality of seafood dealt out from public catering services located in Northeast Italy. In this paper we illustrate the results of microbiological analysis performed on 135 fish samples (58% of samples were raw fishes, 27% cooked fishes, 6% raw fish products, 9% cooked fish products) and species identification performed on 102 fish samples. Additionally, 135 environmental swabs were collected to determine the effectiveness of cleaning and sanitation of food contact (cutting boards, cooking equipment and food processing surfaces) and non-contact (refrigerator wall and handle, tap lever) surfaces. Of raw seafood samples, 24% had total aerobic mesophilic bacteria count >105 CFU/g and for Enterobacteriaceae the faecal contamination was excluded since no Salmonella spp. and Escherichia coli were isolated. Just 3.8% of raw seafood samples resulted positive for Listeria monocytogenes. The results of swab samples of cooking utensils and surfaces showed that sanitation practices should be improved. Molecular analysis for fish species identification revealed a mislabelling for 25% of sampled fishes. The results of this survey can provide valuable information for monitoring and surveillance programmes for the control of quality of fish and fish products.